1978
DOI: 10.3382/ps.0570692
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diet on Liver Glycogen and Body Composition in the Chick

Abstract: Experiments were conducted to study the effects of diet on liver glycogen and body composition in the three-week-old chick. When percent protein and percent lysine were varied, liver glycogen concentration declined significantly as protein and lysine increased, 32.6 vs. 19.4 mg/g for the 14 and 35% protein diets, respectively. Carcass fat decreased and carcass moisture increased in a pattern similar to glycogen as protein and lysine increased in the diets. When seven levels of lysine were fed in isocaloric, is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0
1

Year Published

1980
1980
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 5 publications
4
7
0
1
Order By: Relevance
“…Kondra et al (1962) found that high protein diets produced less abdominal fat when fed to broilers. Similar observations were made by Seaton et al (1978) and Reid and White (1978). Kubena et al (1974b) and Griffiths et al (1977) noted that caloric restriction during the early life of the broiler reduced the amount of abdominal fat at market age.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Kondra et al (1962) found that high protein diets produced less abdominal fat when fed to broilers. Similar observations were made by Seaton et al (1978) and Reid and White (1978). Kubena et al (1974b) and Griffiths et al (1977) noted that caloric restriction during the early life of the broiler reduced the amount of abdominal fat at market age.…”
Section: Resultssupporting
confidence: 87%
“…Griffiths et al (1977) reported that the amount of abdominal fat in male broilers exposed to early caloric restriction was reduced when the protein-calorie ratio of the diet was lowered. Seaton et al (1978) conducted work showing that carcass fat decreased and moisture increased as the percent protein and lysine in the diet increased. Reid and White (1978) reported that body protein was a linear function of body weight, with carcass fat increasing as the protein level of the diet decreased.…”
Section: Introductionmentioning
confidence: 98%
“…The low protein diet decreased carcass and breast percentage during different periods and thigh percentage at 21 days of age (van Nguyen and Bunchasak, 2005;Smith and Pesti, 1998;Attia et al, 2001). The significant effect of energy levels on abdominal fat is similar to the previous study of Seatton et al, (1978) and Attia et al, (1998) found an increasing carcass fat with elevation of energy levels.…”
Section: Carcass Characteristicssupporting
confidence: 80%
“…Thus, liver homogenates may be stored frozen for later analyses provided they are thawed rapidly and analyzed immediately. Our findings for frozen tissue are similar to those of Cleland and Bannister (1979) who found no glycogen decrease after storage at -21 and -70 C. The range of liver glycogen levels reported here are similar to those found by Cleland and Bannister (1979), Seaton et al (1978), Raheja and Linsheer (1978), and Huff et al (1979). As noted by others (Cleland and Bannister, 1979), a large bird to bird variation in glycogen content was found within treatment groups.…”
Section: Resultssupporting
confidence: 94%
“…Glycogen content of chick liver is known to vary considerably with diet (Seaton et al, 1978;Raheja and Linsheer, 1979;Rosebrough et al, 1978). In caged chicks where pecking orders have been established, the variation in rates of feeding may cause variations in levels of liver glycogen.…”
Section: Resultsmentioning
confidence: 99%